NiOx Hole Transport Layer Optimization for Perovskite Solar Cells with Inverted Architecture - Moniz, Mariana Peyró (2022)
In the world of photovoltaic energy, perovskite solar cells (PSCs) are on a very promising path of technological development, since their efficiency progression has been, and still is, quite fast, rising from 3.8% to 25.5% (2020) in only 11 years. Despite the obvious significance of the perovskite absorber layer, the optimization of PSCs also strongly depends on the selective charge transport layers of their hetero-junction architecture, being the hole transport layer (HTL) the one critically needing most research-oriented development. In this thesis, a study was made on the fabrication of NiOx thin-films for their application as HTLs in inverted PSCs (p-i-n layer structure), motivated not only by the proven performance and reliability of NiOx for PSCs but also by its much lower cost relative to other state-of-the-art materials (e.g. Spiro-MeOTAD). With the inverted cell structure, the HTL is deposited prior to the perovskite, thereby allowing the exploration of a broad range of patterning techniques. Here we investigated and optimized NiOx films deposited by rf-sputtering. The fabricated films were analysed by different characterization methods, as UV-Vis-NIR spectrophotometry, X-ray diffraction, and atomic force microscopy. From these analyses, a set of conditions was selected for the integration of the NiOx thin-film in PSCs: 4×10-3 mbar argon pressure, 100 W as rf-power, and 200 ˚C deposition temperature. Batches of PSCs were built over our developed HTLs, chiefly using MAPbI3 active layer, PCBM electron transport layer (ETL), and a BCP buffer layer. The best performance was attained with NiOx deposited with the aforementioned optimized sputtering conditions, resulting in a power conversion efficiency of 10.01%, fill factor of 0.63, open circuit voltage of 0.88V, and short-circuit current density of 17.85 mA/cm2. This achievement is among the state-of-the-art for this class of inverted PSCs, demonstrating the potentialities of physical deposition methods for the HTL application.